Hydrophobicity-induced prestaining for protein detection in polyacrylamide gel electrophoresis. Issue 13 (15th January 2016) - Li, Zhe; Guan, Weijiang; Lu, Chao; Zhou, Xi-Rui; Luo, Shi-Zhong; You, Ying; Ouyang, Jin
Abstract : An aggregation-induced emission fluorescent surfactant has been used to prestain protein by means of strong hydrophobic interaction between fluorescent surfactants and proteins. Abstract : An AIE fluorescent surfactant has been first used to prestain protein by ultrastrong hydrophobic interaction between fluorescent surfactants and proteins, distinguishing from the most widely used poststaining strategies by employing AIE molecules with weak hydrophobic characteristics. A mixture of proteins with variable molecular weights has been detected.